The Composite 259-kb Plasmid of Martelella mediterranea DSM 17316T–A Natural Replicon with Functional RepABC Modules from Rhodobacteraceae and Rhizobiaceae - Bartling, Pascal; Brinkmann, Henner; Bunk, Boyke; Overmann, Jörg; Göker, Markus; Petersen, Jörn (Frontiers in Microbiology, 2017)
A multipartite genome organization with a chromosome and many extrachromosomal replicons (ECRs) is characteristic for Alphaproteobacteria. The best investigated ECRs of terrestrial rhizobia are the symbiotic plasmids for legume root nodulation and the tumor-inducing (Ti) plasmid of Agrobacterium tumefaciens. RepABC plasmids represent the most abundant alphaproteobacterial replicon type. The currently known homologous replication modules of rhizobia and Rhodobacteraceae are phylogenetically distinct. In this study, we surveyed type-strain genomes from the One Thousand Microbial Genomes (KMG-I) project and identified a roseobacter-specific RepABC-type operon in the draft genome of the marine rhizobium Martelella mediterranea DSM 17316T. PacBio genome sequencing demonstrated the presence of three circular ECRs with sizes of 593, 259 and 170-kb. The rhodobacteral RepABC module is located together with a rhizobial equivalent on the intermediate sized plasmid pMM259, which likely originated in the fusion of a pre-existing rhizobial ECR with a conjugated roseobacter plasmid. Further evidence for horizontal gene transfer (HGT) is given by the presence of a roseobacter-specific type IV secretion system on the 259-kb plasmid and the rhodobacteracean origin of 62% of the genes on this plasmid. Functionality tests documented that the genuine rhizobial RepABC module from the Martelella 259-kb plasmid is only maintained in A. tumefaciens C58 (Rhizobiaceae) but not in Phaeobacter inhibens DSM 17395 (Rhodobacteraceae). Unexpectedly, the roseobacter-like replication system is functional and stably maintained in both host strains, thus providing evidence for a broader host range than previously proposed. In conclusion, pMM259 is the first example of a natural plasmid that likely mediates genetic exchange between roseobacters and rhizobia.